PENGARUH MEDIA E-BOOKLET TERHADAP PENGETAHUAN TENTANG PENCEGAHAN ANEMIA PADA REMAJA PUTRI (Jurnal Kesehatan Siliwangi, 2023)
Indonesia is a country with a severe problem of anemia. Furthermore, most anemia in teenagers in Indonesia aged 15-24 years is 32%. In addition, 3-4 out of 10 teenage in Indonesia suffer from anemia. Furthermore, nutrient intake inequality is the cause of anemia in teenage women. The scope of providing iron tablets to teenage women, only 2.13% accept iron tablets as instructed. Hence, it is necessary to prevent anemia by using exciting media. Therefore, it is required to avoid anemia in teenage women using the E-Booklet media. This study aimed to analyze the influence of E-Booklet media on anemia prevention in teenage women's knowledge at MA, Bandung Regency. This type of research is Quasi Experiment design with One Group Pretest-Posttest design research. The instrument used in calculating knowledge was a questionnaire. Furthermore, samples were 35 students, and the sample group was selected using the Propionate Stratified Random Sampling technique. Furthermore, the data analysis used was Paired T-test. The analysis results showed a significant difference in the increase in knowledge that the value of the p-value was = 0.000. At the same time, the average increase in the knowledge score of respondents was 19.52. Thus, it can be concluded that the E-Booklet media affects the prevention of anemia in teenage women's knowledge at MA, Bandung Regency.